MENGOPTIMALKAN PEMBELAJARAN BAHASA INGGRIS MELALUI STRATEGI MEMBACA BERBASIS BAHASA ISYARAT BAGI SISWA INKLUSI - Ramanda Rizky; Meta Silfia Novembli; Nisaul Hasanah; Ibra Naziva Salwa; Dini Muktia Roza (Smart Education, 2025)
Abstract: The pressing need for innovative methods in English language learning for deaf students has so far faced serious obstacles due to the limited number of educators with English language degrees. This condition causes the learning methods and media used tend to be less varied and not in accordance with the special needs of students, resulting in low vocabulary mastery and weak text comprehension skills. To answer this challenge, the PkM team from Lancang Kuning University designed a sign language-assisted reading strategy training. The approach is visual and interactive, integrating skimming, scanning and predicting techniques with sign language to help students visualize the meaning of words while understanding the context of the text. The program evaluation proved the effectiveness of this approach. The average reading comprehension score increased significantly from 45.6 (pre-test) to 82.3 (post-test). In addition, field observations showed an increase in students' motivation, enthusiasm and active participation. The highest indicators were on understanding the main idea (96.25%) and cause-and-effect relationship (94.05%), indicating that this strategy not only strengthens vocabulary acquisition, but also logical and analytical thinking skills. These results confirm that a multisensory approach that combines conventional reading strategies with sign language is an effective solution to improve deaf students' English literacy. Furthermore, this success emphasizes the importance of professional training for teachers so that similar practices can be widely and sustainably implemented in inclusive and special schools.Â Keyword: Sign Language; Reading Strategy; Disability Students..Â Abstrak: Kebutuhan mendesak akan metode inovatif dalam pembelajaran bahasa Inggris bagi siswa tunarungu selama ini masih menghadapi hambatan serius akibat keterbatasan tenaga pendidik lulusan bahasa Inggris. Kondisi tersebut menyebabkan metode dan media pembelajaran yang digunakan cenderung kurang variatif dan tidak sesuai dengan kebutuhan khusus siswa, sehingga berdampak pada rendahnya penguasaan kosakata serta lemahnya kemampuan memahami teks. Untuk menjawab tantangan ini, tim PkM dari Universitas Lancang Kuning merancang pelatihan strategi membaca berbantuan bahasa isyarat. Pendekatan ini bersifat visual dan interaktif, mengintegrasikan teknik skimming, scanning, dan predicting dengan bahasa isyarat untuk membantu siswa memvisualisasikan makna kata sekaligus memahami konteks teks. Evaluasi program membuktikan efektivitas pendekatan ini. Rata-rata skor pemahaman bacaan meningkat signifikan dari 45,6 (pre-test) menjadi 82,3 (post-test). Selain itu, observasi lapangan menunjukkan peningkatan motivasi, antusiasme, dan partisipasi aktif siswa. Indikator tertinggi terdapat pada pemahaman gagasan utama (96,25%) dan hubungan sebab-akibat (94,05%), yang menandakan bahwa strategi ini tidak hanya memperkuat penguasaan kosakata, tetapi juga keterampilan berpikir logis dan analitis. Hasil tersebut menegaskan bahwa pendekatan multisensori yang memadukan strategi membaca konvensional dengan bahasa isyarat merupakan solusi efektif untuk meningkatkan literasi bahasa Inggris siswa tunarungu. Lebih jauh, keberhasilan ini menekankan pentingnya pelatihan profesional bagi guru agar praktik serupa dapat diimplementasikan secara luas dan berkelanjutan di sekolah inklusi maupun sekolah luar biasa.Â Kata kunci: Bahasa Isyarat; Reading Strategy; Siswa Berkebutuhan Khusus.